SETTLEMENTS OF THE JALAL-ABAD REGION THAT HAVE RECEIVED CITY STATUS IN RECENT YEARS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the article, the cities of Jalal-Abad region, which received the status of cities in the years of independence, are analyzed, socio-economic changes, demographic trends, as well as factors influencing the development of these settlements. It is a historical fact that the cities were the centers of economy, science, education and high culture, and therefore the cities went through different paths in their origin, formation and development, and as a result of culture, education, health care and highly developed social conditions, today they achieve great achievements as centers of civilization. There is no doubt that the cities of the region under consideration have been relatively prosperous compared to other regions of Kyrgyzstan since their foundation.
Keywords: Jalal-Abad region, Kochkor-Ata, Kerben, Toktogul, Bazar-Korgon, Shamaldy-Sai, cities, state, community, development, socio-economic, local, organization